2023
DOI: 10.1017/wsc.2023.36
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and classification of urban weed species in northeast China using terrestrial hyperspectral images

Jinfeng Wang,
Guoqing Chen,
Jinyan Ju
et al.

Abstract: Weeds contribute to biodiversity and a wide range of ecosystem functions. It is crucial to map different weed species and analyze their physiological activities. Remote sensing techniques for plant identification, especially hyperspectral imaging, are being developed using spectral response patterns to vegetation for detection and species identification. A library of hyperspectral images of 40 urban weed species in northeast China was established in this study. A terrestrial hyperspectral camera was used to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…The 680-750 nm (red-edge) and 700 nm bands are related to chlorophyll. Many weak peaks were recorded at 760-980 nm, mainly reflecting the tensile vibration of the third overtone of the O-H bond and C-H bond [38]. From the results obtained, it can be concluded that these observed differences can further serve as the basis for determining LNCs in wheat.…”
Section: Preliminary Investigation By Pcamentioning
confidence: 89%
“…The 680-750 nm (red-edge) and 700 nm bands are related to chlorophyll. Many weak peaks were recorded at 760-980 nm, mainly reflecting the tensile vibration of the third overtone of the O-H bond and C-H bond [38]. From the results obtained, it can be concluded that these observed differences can further serve as the basis for determining LNCs in wheat.…”
Section: Preliminary Investigation By Pcamentioning
confidence: 89%